PRODUCTION FACTORS EFFECT ON GILL NET FISHERMEN CATCH IN INNER AMBON BAY - Sangadji, Selfi; Tupamahu, Agustinus; Hehanussa, Kedswin (Departemen PSP IPB, 2025)
The observed decline in fishery production within the Teluk Ambon and Teluk Ambon Baguala sub-districts of Ambon City from 2020 to 2021 has prompted concerns regarding the efficacy of the fishing gear employed, particularly gill nets, which are predominantly utilized by small-scale fishers in Teluk Ambon Dalam. This study sought to examine the impact of various production factors on the catch yields of fishermen using gill nets, specifically focusing on net length, net width, frequency of fishing trips, immersion duration, and the experience of the fishermen. A descriptive methodology was employed, utilizing a survey technique for primary data collection through structured interviews with 12 respondents, complemented by secondary data sourced from official records and scientific literature. The analysis revealed that, although not all variables demonstrated statistical significance, there existed a positive correlation between certain technical factors and the total catch, notably net width, frequency of fishing trips, and fishermen's experience. These findings underscore the necessity of optimizing production variables as a strategic approach to enhance the efficiency and sustainability of small-scale fisheries in coastal regions. Key words: fishing operations, passive fishing gear, productivity, small-scale fisheries, technical variable